A Sex Difference in the Effect of Aspirin on “Spontaneous” Platelet Aggregation in Whole Blood - Harrison, M J G; Weisblatt, E (Thrombosis and Haemostasis, 1983)
Platelet aggregation can be measured in whole blood by monitoring the fall in single platelet count in an electronic platelet counter. The aggregation that occurs when whole blood is stirred in a small cuvette (“spontaneous aggregation”) or upon the addition of collagen has been studied in citrated whole blood from male and female volunteers. Aspirin 40 μg ml/1 inhibited aggregation induced by collagen in both sexes but spontaneous aggregation was only affected by aspirin in males. These results may help explain the sex difference apparent in the results of some clinical trials of aspirin as an antithrombotic agent.
Keywords: Platelet aggregation; Aspirin; Whole blood aggregation Sex difference